The waltzes for piano by Chiquinha Gonzaga: a pedagogical overview - Simões, Ana Paula M. (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
This paper aims to investigate the waltzes for piano by Francisca Gonzaga to identify their main characteristics and the musical, technical, and reading challenges that piano students will encounter when practicing her pieces. All waltzes were performed, analyzed, and compared to pieces graded by Jane Magrath (1995) in order to be classified in a level of difficulty from one to ten. Here, their main characteristics are discussed and one waltz of each level is presented and analyzed as an example. It was observed that the levels of difficulty of Gonzaga’s waltzes range from six to ten and that they feature various technical and musical demands that can prepare students for a more advanced repertoire, such as pieces by Romantic composers. Chiquinha was an important female personality and her output deserves more recognition, not only for its historical importance and intrinsic quality but also for its pedagogical value. This paper intends to promote her works and stimulate piano teachers to include her pieces in the repertoire of their students.